The Implementation Of Marriage Different Religion And Their Due To The Law Of The Religion Of Marriage Status - Prasasti Dyah Nugraheni (Law and Justice, 2019)
Marriage is a very strong and very deep bond that functions to connect between a man and a woman in a household or a family. Informing a household or a family, the belief in the same religion requires not only confidence in the same commitment. However, in the life of the Indonesian people, there are currently many marriages that are not based on similarities in religious beliefs. The marriage is only based on genuine love between a man and a woman. These different religious marriages cause problems in the legal field such as the validity of the marriage itself according to the marriage law in force in Indonesia. Because according to Article 2 Paragraph (1) of Law Number 1 the Year 1974 marriage which is called legitimate is a marriage which is carried out in accordance with the religion and beliefs of the person. Marriage with different religions also causes problems with the legitimacy of the representation. So the problem that will be explained in this journal is about the validity of a marriage that is of different religions in accordance with Law Number 1 of 1974. According to Law Number 1 of 1974 marriages of different faiths is an illegitimate marriage because they are not in accordance with religion and belief in Indonesia. Because according to Article 2 Paragraph (1) of Law Number 1 of 1974 it is stated that if a religion allows the marriage of a different religion, then the marriage is permissible. However, if a religion does not allow the marriage that is of a different religion, then the marriage is not allowed. Keywords: Interfaith marriage, Law Number 1 of 1974, and Compilation Islamic Law